Dru C. Gladney (ed.): Making Majorities. Constituting the Nation in Japan, Korea, China, Malaysia, Fiji, Turkey, and the United States - Fischer, John (Tidsskriftet Antropologi, 1999)
Korea, China, Malaysia, Fiji, Turkey, and the United States. Anmeldes af Johan Fischer